The Effect of Competence And Work Environment On Teacher Performance At SMAN 4 of Bengkulu City - Yollandah Yollandah; Ida Anggriani; Nia Indriasari (Penerbit Jurnal Indonesia, 2023)
This research aims to determine the effect of competence on teacher performance at SMAN 4 of Bengkulu City, to determine the effect of work environment on teacher performance at SMAN 4 of Bengkulu City, and to determine the effect of competence and work environment on teacher performance at SMAN 4 of Bengkulu City. The data collection method in this research is using a questionnaire and the analysis method is multiple linear regression. Based on the research results, it was found that competence had a significant effect on teacher performance at SMAN 4 of Bengkulu City because the significance value was 0.000 < 0.05. The work environment has a significant effect on teacher performance at SMAN 4 of Bengkulu City because the significance value is 0.001 < 0.05. Competence and work environment have a significant effect on teacher performance at SMAN 4 of Bengkulu City because the significance value is 0.000 < 0.05